Idea of Collateral and Guarantor in Islamic Bank Financing - Idris Yahaya Adamu (SEISENSE (PRIVATE) LIMITED, 2018)
This study explores the idea of Islamic banks requesting for collateral or guarantee when financing, the rationale for requesting loan security, and its acceptability from Islamic perspectives. The study reviewed the previous literature and Islamic injunctions to study and justify the use of collateral and guarantor to hedge the risk of financing default. It is found that Islamic banks like conventional banking system encourage requesting loan security to ensure borrowers’ commitment and protect investors’ wealth. Despite its effect on loan rejection, secured loans are found to be recovered more easily than unsecured loans. Government and Islamic banks are therefore advised to device mean for helping small-scale businesses to access financing, through credit guarantee schemes and participatory financing mechanisms, to enhance financial inclusion.